CHARACTERISTICS OF EDIBLE FILM (LAYER BY LAYER) FROM CARRAGEENAN-CHITOSAN WITH THE ADDITION OF BELIMBING WULUH LEAF EXTRACT AS ANTIOXIDANT SUBSTANCE - Rahmah Isnaeni; Anisa Fitri; Desi Nurandini; Arif Tirtana; Muhmmad Zeva Prayitno (Konversi, 2022)
Packaging use from synthetic materials can have a negative impact for environment. One of the steps to reduce this impact with edible film packaging uses. Film can be defined as a thin layer of material, that usually composed by a polymer that allows for mechanical strengthening of a structured stand. The quality that continues to be improved from the edible film is antioxidant activity, namely by adding antioxidant substances such as flavonoids and phenols from starfruit leaf extract. As well as improving its mechanical quality by adding shrimp shell chitosan and using the layer by layer method. The purpose of this research is to find out characteristics of edible film from carrageenan-chitosan layer by layer and find the best results from the addition of different concentrations of chitosan and Belimbing Wuluh leaf extract. The variation that will be carried out is the addition of Belimbing Wuluh leaf extract by 0.2%, 0.4% and 0.6% and chitosan by 1.5%, 2% and 2.5%. The results showed that the best formula of edible film was made from 2.5% chitosan concentration and 0.6% Belimbing Wuluh leaf extract. The results of test are the thickness test is 0.21 mm, the tensile strength is 2.87 MPa, the elongation at break is 13.6673%, the water vapor permeability is 2.1682 g/m2h and the antioxidant value in terms of fruit weight loss is 4.01%.